Коллективная обида: к вопросу определения феномена - Музылѐв, Александр; Muzylov, Oleksandr; Музильов, Олександр (Східноєвропейський національний університет імені Лесі Українки, 2019)
Наличие боевых действий на территории страны, политический и религиозный кризис являются благоприятными обстоятельствами для появления и конструирования коллективной обиды. В статье освещается разница между примордиалистскими и конструктивистскими подходами к пониманию коллективной обиды. Теоретический анализ с использованием концепции М. Хальбвакса позволяет выявить, какие именно аспекты в коллективной обиде могут быть сконструированы – представление о прошлом, образ врага. Выявляется взаимосвязь с родовыми понятиями – коллективная память и культурная травма. В статье представлены традиционные и новые формы демонстрации коллективной обиды, среди которых – политические заявления, резолюции, акции протеста, вандализм, публикации в социальных сетях, санкции, использование художественных средств для демонстрации и конструирования коллективной обиды. The article deals with the phenomenon of collective resentment, as well as related concepts: collective memory, cultural trauma. Favorable circumstances have now developed in Ukraine (hostilities are underway in the country, a crisis in the sphere of politics and religion is also appearing) for the emergence and construction of a collective resentment. However, the phenomenon itself is poorly studied, so it is important to study its features, the specifics of its appearance and how it is manifested in practice. For this purpose, we analyze primordialist and constructivist approaches to the study of collective resentment. It has been revealed that constructivism better describes this phenomenon, since even within the same society individuals may have different resentments. Using the Halbwachs concept, it is possible to identify the relationship between collective resentment and tribal concepts – collective memory and cultural trauma. Collective resentment is seen as a result of cultural trauma, as well as its further construction with the help of the media, agents of resentment actualization, artworks, and memorial events. Cultural trauma becomes a part of collective memory and its repeated reproduction (e.g., the annual memory day of war victims) contributes to the formation and maintenance of the current state of collective resentment. Whereas collective resentment used to be manifested in pogroms, wars and other violent methods, the situation is changing now. It is reaching the diplomatic level. Politicians are called upon to express collective grievances, and by adopting laws and regulations, they actually legitimize them. Demonstration is important for collective resentment, so social networks are used to convey information to as many audiences as possible and to contribute to the construction of resentment. They provide information about an event or a day of remembrance. Collective resentment can be the basis of identity and it is precisely this that establishes «boundaries» between representatives of different social, cultural and ethnic groups, which only aggravates existing divisions and contributes to the further polarization of different groups, and this can occur even within the same society.
Collective Resentment: to the Issue of Defining the Phenomenon
Keywords: коллективная обида; коллективная память; культурная травма; идентичность; радикализ; collective resentment; collective memory; cultural trauma; identity; radicalism